Lifelong occupational exposures and hearing loss among elderly Latino Americans aged 65–75 years. (February 2015) - Hong, OiSaeng; Chin, Dal Lae; Kerr, Madeleine J.
Abstract: Objective: The purpose of this study is to determine the relationship between occupational exposures and hearing among elderly Latino Americans. Design: A descriptive, correlational design used for this secondary analysis with the data from the Sacramento Area Latino Study of Aging (SALSA). Study sample: A total of 547 older adults were included. Results: A majority of participants (58%) reported occupational exposures to loud noise and/or ototoxic chemicals. About 65% and over 90% showed hearing loss at low and high frequencies, respectively. Participants with occupational exposure to loud noise and/or ototoxic chemicals were, significantly, two times more likely to have hearing loss at high frequencies compared to those without exposure (OR = 2.29; 95% CI: 1.17 = 4.51, p = .016), after controlling for other risk factors of hearing loss such as age, gender, household income, current smoking, and diabetes. However, lifelong occupational exposure was not significantly associated with hearing loss at low frequencies (OR = 1.43; 95% CI: 0.94 = 2.18, p = .094). Conclusion: Lifelong occupational exposure to loud noise and/or ototoxic chemicals was significantly associated with hearing loss among elderly Latino Americans. Healthy work life through protection from harmful auditory effects of occupational exposures to noise and chemicals will have a positive impact on better hearing in later life.